Tingkat Literasi Informasi Mahasiswa Angkatan 2022 dalam Penggunaan Platform E-Commerce Shopee di Fakultas Bahasa dan Seni Universitas Negeri Padang - Helwina Aysha Putri; Nurizzati Nurizzati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study is motivated by the importance of information literacy among students in using the Shopee e-commerce platform. The purpose of this study is to determine the level of information literacy of 2022 cohort students at the Faculty of Languages and Arts, Padang State University, in using the platform e-commerce Shopee. This research employs a quantitative approach with a descriptive method. The population in this study consists of all 2022 cohort students of the Faculty of Languages and Arts, Padang State University, totaling 1,208 students, with a sample of 92 respondents selected using a simple random sampling technique based on the Slovin formula. Data collection in this study was conducted using a questionnaire developed based on the The Seven Faces of Information Literacy model, which was distributed online via WhatsApp in the form of Google Forms and directly through QR codes.Based on the confidence interval calculation, the average level of students’ information literacy falls within the range of 3.05 < μ < 3.27, indicating that the information literacy level of 2022 cohort students in using the platform e-commerce Shopee at the Faculty of Languages and Arts, Padang State University, is categorized as high. In general, it can be concluded that students have a good level of information literacy, particularly in aspects of information technology use, utilization of information sources, information searching processes, information control, knowledge construction, knowledge development, and wisdom in using information on the Shopee e-commerce platform.